Prognostic Value of Transcranial Doppler in the Survival of Patients with Spontaneous Cerebral Intraparenchymal Hemorrhage - Julio López Argüelles; Erélido Hernández Valero (Revista Finlay)
Background: transcranial doppler is a technique which is constantly being developed and constitutes an indirect measure of intracranial pressure. Objective: to demonstrate the prognostic value of transcranial doppler in patients with spontaneous cerebral intraparenchymal hemorrhage. Method: a prospective study was carried out on 50 patients admitted with the diagnosis of intraparenchymal cerebral hemorrhage of non-traumatic cause in the first 12 hours of admission, the pulsatility rate and average velocity in the middle cerebral artery was determined bilaterally. A univariate study was performed at age, presence of intraventricular blood, average speed, hematoma volume and transcranial doppler values. The existence of correlation between the pulsatility index values and average speed with the average speed was evaluated. The values of transcranial doppler were found their predictive values. Results: a significant association was obtained among hematoma volume, transcranial doppler values and electrocardiogram with survival. In addition, a correlation was found between this last parameter and the transcranial doppler. The area under the operating characteristic curve of the transcranial doppler receptor in the affected hemisphere was highly predictive of mortality with high sensitivity and specificity for cut-off points of the pulsatility index at 1.85 and average speed at 32.3 cm/s. Conclusions: glasgow coma scale and hematoma volume are the main prognostic indicators of survival in patients with spontaneous intraparenchymal hemorrhage.